The changes in family law in Czechoslovakia in the interwar period - Renata Veselá (Journal on European History of Law)
The article contains the description of legal regulation of the family law during 1918 – 1938 in the first Czechoslovak republic. The basic theme are the Act of divorce (320/1919) and the attempts of preparing of the new Civil code including family law during that time.